Low-dose vs. standard-dose alteplase for Chinese patients with acute ischemic stroke: A propensity score analysis - Xu, Jiawen; Chen, Xi; Xie, Yanan; Wang, Yi; Chen, Shidong; Dong, Qiang; Dong, Yi; Fang, Kun (Frontiers in Neurology, 2023)
Background and purpose Previous studies have stimulated debates on low-dose alteplase administration in acute ischemic stroke (AIS) among the Asian population. We sought to evaluate the safety and efficacy of low-dose alteplase in Chinese patients with AIS using a real-world registry. Methods We analyzed data from the Shanghai Stroke Service System. Patients receiving alteplase intravenous thrombolysis within 4.5 hours were included. These patients were divided into the low-dose alteplase group (0.55–0.65 mg/kg) and the standard-dose alteplase group (0.85–0.95 mg/kg). Baseline imbalances were adjusted by using the propensity score matching. The primary outcome was mortality or disability, which was defined as the modified Rankin scale (mRS) score ranging from 2 to 6 at discharge. The secondary outcomes were in-hospital mortality, symptomatic intracranial hemorrhage (sICH) and functional independence (mRS score 0–2). Results From January 2019 to December 2020, a total of 1,334 patients were enrolled and 368 (27.6%) were treated with low-dose alteplase. The median age of the patients was 71 years, and 38.8% were female. Our study showed that the low-dose group had significantly higher rates of death or disability (adjusted odds ratio (aOR) = 1.49, 95% confidence interval (CI) [1.12, 1.98]) and less functional independence (aOR = 0.71, 95%CI [0.52, 0.97]) than the standard-dose group. There was no significant difference in sICH or in-hospital mortality between the standard-dose and low-dose alteplase groups. Conclusions Low-dose alteplase was related to a poor functional outcome without lowering the risk of sICH, compared with standard-dose alteplase for AIS patients in China.